Ultra-wideband planar antenna with notched-band for WIMAX, WLAN and MSAT applications - Siti Fatimah Jainal; Norliza Mohamed; Azura Hamzah; Suhaila Subahir (Penerbit Universiti Kebangsaan Malaysia, 2020)
Ultra-wideband (UWB) with triple band notch characteristics was presented. WIMAX, WLAN and Meteorological Satellite (MSAT) frequency bandwidths were rejected in the UWB planar antenna composed from a single layer conductor element. Frequency bandwidths for WIMAX, WLAN and MSAT are allocated at 3.3~3.7, 5~6 and 7.4~8.4GHz, respectively. Conductor element etching method was used as the means to realize the band notch characteristics as it was considered convenient and simple. Two slits were etched on the ground plane while on the elliptical element, a single slit. The slits were designed for simplicity in the means of achieving the desired band notch characteristics. The proposed antenna design was compact and low profile. The antenna performances were compared with the reference antenna and the results were negligible.